Innovation and International Entrepreneurship: Will the Digital Platform Serve All? - Rammal, Hussain G. (International Journal of Economics, Business, and Entrepreneurship, 2019)
The link between knowledge, innovation, and technology, as understood in extant literature, tends to emphasize a digital, high-tech platform for the implementation of innovative ideas. This paper challenges this view and details why relying solely on digital platforms and innovation may not let companies reach their full potential. Using examples of frugal innovation, this paper recommends that entrepreneurs need not limit their ideas by focusing only on digital and technology-driven innovation, and to consider the infrastructure realities of the developing economies.